Theoretical aspects of depreciation methods of use of the main resources for ensuring public requirement. (Journal of Economic Research & Business Administration, 2015)
In our country the market economy develops thanks to systematically held events of economic policy. The solution of problems of improvement of labor productivity and formation of competitiveness will influence economy growth, will give the chance to improve financial and economic system because depreciation is a process of transfer of cost of fixed assets on the cost of the made and sold end products.Therefore updating of means, tools of the highest scientific and technical level becomes a basis of economic growth of the country, the industry. Taking into account all these momentsin this article use of the accelerated methods of the depreciation policy directed on economic growth and ensuring public requirement is offered that in turn increases the annual sum of the main resources, accelerates updating of the main resources, reduces the volume of taxes, interferes with inflation.
Keywords: norm of depreciation; sinking fund; depreciation нормасы; capital cost; advance cost; tax norm of depreciation; depreciation charges